Media, metaphors and modeling: how the UK newspapers reported the epidemiological modelling controversy during the 2001 foot and mouth outbreak - Nerlich, Brigitte (Sage, 2007)
The relation between theoretical models and metaphors has been studied since at least the 1950s. The relation between metaphors and mathematical modelling is less well researched. This article takes the media coverage of the foot and mouth modelling exercise in 2001 as an occasion to examine the metaphors of mathematical modelling that were proposed by the UK press during that time to make sense of this new scientific policy tool. One can detect a gradual change in metaphor use by the newspapers from conceptualizing modellers as detectives and models as mapping tools to modellers as soldiers and heroes, to modellers as liars and models as tools to distort the truth. This seems to indicate a shift in reporting from seeing models as a legitimate and "objective" basis used by decision makers to pursue science-based policies towards seeing models as tools used to legitimize increasingly difficult political decisions.